Backup and Restore of SQL Server Databases (SQL Server 2012 Books Online) (Microsoft, 2015)
This topic describes the benefits of backing up SQL Server databases, basic backup and restore terms, and introduces backup and restore strategies for SQL Server and security considerations for SQL Server backup and restore. The SQL Server backup and restore component provides an essential safeguard for protecting critical data stored in your SQL Server databases. To minimize the risk of catastrophic data loss, you need to back up your databases to preserve modifications to your data on a regular basis. A well-planned backup and restore strategy helps protect databases against data loss caused by a variety of failures. Test your strategy by restoring a set of backups and then recovering your database to prepare you to respond effectively to a disaster...